2020
DOI: 10.3390/nu12123833
|View full text |Cite
|
Sign up to set email alerts
|

The Diverse Efficacy of Food-Derived Proanthocyanidins for Middle-Aged and Elderly Women

Abstract: Middle-aged and elderly women are affected by various symptoms and diseases induced by estrogen deficiency. Proanthocyanidins, widely present in many kinds of fruits and berries, have many beneficial effects, such as antioxidative, anti-inflammatory, and antimicrobial activities. We researched the effects of proanthocyanidins for middle-aged and elderly women, finding that it has been revealed in many clinical trials and cohort studies that proanthocyanidins contribute to the prevention of cardiovascular disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 93 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…The results of the study show a significant improvement in some characteristics of the egg for the third, fourth and fifth treatments (relative weight of the shell and thickness of the shell) Table 7 and the fourth and fifth treatments (white height, hue unit) Table 8, with regard to the significant improvement in the relative weight of the shell, it may be attributed to an increase and with respect to height Whiteness and unity, and with regard to high whiteness and unity, and with regard to weight gain, and ziure, female sex hormones [18], estrogens are female hormones that work to increase the secretion of tubular glands, including protein and proteins, egg white proteins [19] .which are egg white proteins on the egg white which is part of the oviduct. Eggs and whites are a unit dependent on the height of the egg white.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the study show a significant improvement in some characteristics of the egg for the third, fourth and fifth treatments (relative weight of the shell and thickness of the shell) Table 7 and the fourth and fifth treatments (white height, hue unit) Table 8, with regard to the significant improvement in the relative weight of the shell, it may be attributed to an increase and with respect to height Whiteness and unity, and with regard to high whiteness and unity, and with regard to weight gain, and ziure, female sex hormones [18], estrogens are female hormones that work to increase the secretion of tubular glands, including protein and proteins, egg white proteins [19] .which are egg white proteins on the egg white which is part of the oviduct. Eggs and whites are a unit dependent on the height of the egg white.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that plant polyphenols, functioning as natural antioxidants, have the potential to improve gut health and mitigate metabolic disease (Del Rio et al., 2013; Fraga et al., 2019). GSE‐derived proanthocyanidins contribute to the prevention of many diseases for middle‐aged and older women, including OP (Izumi & Terauchi, 2020). Studies have revealed that proanthocyanidins can promote osteogenic differentiation in dexamethasone‐treated osteoblasts by inhibiting oxidative stress, mitochondrial dysfunction and apoptosis (Chen et al., 2020), and proanthocyanidins inhibit osteoclast formation via suppressing the nuclear factor kappa B (NF–κB) and c‐Jun N‐terminal kinase (JNK) signalling pathway (Kwak et al., 2020; Zhu et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…3.1.12 | Grape seed (Vitis vinifera) and pine bark Proanthocyanidins (naturally occurring polyphenolic compounds), which are found in both grape seed and pine bark, help to improve menopausal symptoms and regulation of bone homeostasis (Izumi & Terauchi, 2020). It possesses free radical-scavenging property against oxidative stress and is responsible for its desired pharmacological action (Vitseva et al, 2005).…”
Section: Green Tea (Camellia Sinensis)mentioning
confidence: 99%